Analysis of the Effects of Work Method Selection and Monitoring of Work Execution on Construction Time and Cost Risks in Highway Projects - Damar Kurnia; Acep Hidayat; Mawardi Amin (Green Publisher Indonesia, 2026)
This research aims to analyze the effect of work method selection and work implementation monitoring on time and cost risks in toll road construction projects in Banten Province. Toll road construction projects have a high level of complexity and frequently face various problems, such as project delays, cost overruns, limited resources, and weak project supervision systems. These conditions underscore the importance of implementing appropriate work methods and effective project monitoring to minimize risks during construction activities. This study employed a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected through questionnaires distributed to 54 respondents consisting of contractors, supervisory consultants, and project management personnel involved in toll road projects in Banten Province. Data analysis was conducted using SmartPLS 4 software through outer model and inner model testing. The results show that work methods have a negative and significant effect on both time risk and cost risk. Furthermore, project monitoring also has a negative and significant effect on both time risk and construction cost risk. The findings indicate that the better the implementation of work methods and project monitoring, the lower the risks of project delays and cost overruns. This study is expected to serve as a reference for contractors, consultants, and project owners in improving the effectiveness of toll road construction project management, particularly in controlling project time and costs.